Objetos y cultura. Rituales, flujos y elaboraciones en el Nuevo Reino de Granada. - Orián Jiménez Meneses. (Historia Crítica, 2009)
This article studies the circulation, appropriation, and commercial and symbolic uses of objects in colonial society, suggesting ways to understand the circulation of objects and commodities through the spaces of the New Kingdom of Granada. It tries to specify the functions played by objects in domestic life and, based on their circulation, to weave together the communications they established between cities, towns, and settlements and the centers of power in Antioquia and the Viceroyalty during the eighteenth century. By going behind the historicity of the objects, the marks they made and their creation, we can better understand the dimensions of their routes, circuits, and nodes as a substantial part of the culture and the relations of interdependence with other societies.